1994
DOI: 10.1177/003368829402500201
|View full text |Cite
|
Sign up to set email alerts
|

Examining Learners' Language Learning Strategies

Abstract: A number of researchers have examined variables/factors that affect the choice of language learning strategies. Some of the variables, such as language teaching method, language learning level, field of specialization at Harvard Libraries on July 23, 2015 rel.sagepub.com Downloaded from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…More importantly, regarding the cultural background of the participants in the current study, Sy (1994) concluded that female EFL students in China showed greater use of cognitive, metacognitive, and social strategies. In another Asian study, Hashim and Sahil (1994) found that Malaysian females (of Chinese, Malay, and Indian ethnic backgrounds) favored affective strategies more than males; however, no significant differences were observed in other strategy categories. To obtain more data on the influence of gender on both strategy use and proficiency, Green and Oxford (1995) have called for more studies from other cultures.…”
Section: Gendermentioning
confidence: 88%
See 2 more Smart Citations
“…More importantly, regarding the cultural background of the participants in the current study, Sy (1994) concluded that female EFL students in China showed greater use of cognitive, metacognitive, and social strategies. In another Asian study, Hashim and Sahil (1994) found that Malaysian females (of Chinese, Malay, and Indian ethnic backgrounds) favored affective strategies more than males; however, no significant differences were observed in other strategy categories. To obtain more data on the influence of gender on both strategy use and proficiency, Green and Oxford (1995) have called for more studies from other cultures.…”
Section: Gendermentioning
confidence: 88%
“…Interestingly, a SILL EFL/ESL study in Malaysia (Hashim & Sahil, 1994) found that apart from the SILL category of affective strategies, which women favored significantly more, no other significant differences were observed in the other SILL categories. Although the number of the bilingual participants was not reported, many were certainly experienced L2 learners due to the ethnic composition of both the sample and the population in Malaysia.…”
Section: Strategy Use and Gendermentioning
confidence: 95%
See 1 more Smart Citation
“…(Kohonen, 1992, p,24) Several researchers (e.g. Awang Hashim & Syed Sahil, 1994;O'Malley & Chamot, 1990;Sharkey, 1994-95) claim the need to provide more information about language learning strategies or to teach them directly. Holmes and Ramos (1991) state that in order to help learners assume greater control over their own learning it is important to help them to become aware of and identify the strategies that they already use or could potentially use.…”
Section: Learning Strategy Usementioning
confidence: 99%
“…In addition to the changes in the environment, because of increasing attention paid to learner characteristics, the teacher-centered model in English teaching is shifting to a learner-centered model (Chen & Jonas, 2009;Hashim & Sahil, 2010;Kamalizad & Jalilzadeh, 2011;Nyikos & Oxford, 1993). Learning a foreign language can be a complex and lifelong process.…”
Section: Introductionmentioning
confidence: 99%